The Effect of Capital Intensity, Inventory Intensity, and Profitability on Tax Avoidance at PT Mayora Indah Tbk for the Period 2018–2025 - Michelle Angela Gunawan; Sylvia Fettry Elvira Maratno (Surplus: Jurnal Ekonomi dan Bisnis, 2026)
Taxes are strategic fiscal instruments that create conflicting interests between government and companies, leading to tax avoidance practices. This study aims to analyze the effect of capital intensity, inventory intensity, and profitability on tax avoidance at PT Mayora Indah Tbk during 2018–2025. This research employs a quantitative descriptive method with secondary data from quarterly financial reports. The population is PT Mayora Indah Tbk, with 30 quarterly observations as the sample. The research instruments are capital intensity (fixed assets to total assets), inventory intensity (inventory to total assets), profitability (Return on Assets), and tax avoidance (Effective Tax Rate). Data analysis uses multiple linear regression, F-test, t-test, and R-square. Results show capital intensity significantly negatively affects tax avoidance (p=0.000003), while inventory intensity (p=0.0848) and profitability (p=0.5150) are not significant. The model explains 59.64% of tax avoidance variation. In conclusion, capital intensity is the dominant factor driving tax avoidance through depreciation expense utilization, whereas inventory intensity and profitability do not significantly influence tax avoidance behavior at this company.